CFSP after the footnote summit - Annegret Bendiek (Stiftung Wissenschaft und Politik (SWP), 2007)
At the European Council summit in June 2007 the heads of state and government agreed to create the office of a High Representative of the Union for Foreign Affairs and Security Policy and an External Action Service. Yet, at the same time several of the 23 footnotes of the Presidency Conclusion stressed that neither the responsibilities of the member states for their foreign policy nor of their national representation in third countries and international organisations shall be affected in the future. Pro-integrationists like Luxemburg and Italy criticised the outcome of the summit since it does not foresee to transfer further foreign and security policy competences to the EU-level
Keywords: 320